Study on Naturopathic Medical Students’ Perspective on Vaccination and Naturopathy Practice in Ghana: A Review - Obu, Raphael Nyarkotey; Aggrey –Bluwey, Lawrencia (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Background: In Ghana, the subject of vaccination in the COVID-19 pandemic has become a contentious issue. As enshrined in public health principles, vaccination and Naturopathy are comparable, and Naturopathic students study public health as a discipline.Many persons in Ghana call themselves Naturopathic Doctors, however they do not believe in Naturopathy's embrace of public health fundamentals like vaccination. Are vaccinations also naturopathic? Objectives: The knowledge and awareness of vaccinations in Naturopathic practise among Ghanaian Naturopathic Medical Students is examined in this case study. Methods: The study used a qualitative approach to collect primary data from respondents via a drafted questionnaire. The survey consisted of a series of questions that were given to ten (10) people.Naturopathic Medical Students from Ghana's Nyarkotey College of Holistic Medicine were chosen as respondents for this study. Results: Vaccines, according to the Naturopathic medical students, are a part of the Naturopathic profession and are consistent with Naturopathic principles. Surprisingly, only one of the ten respondents received the COVID-19 vaccine in Ghana. The remainder, on the other hand, have expressed an interest in receiving the vaccine but are waiting to see how the side effects play out before making a final decision. Conclusion: Naturopathic Medical students have adequate knowledge and understanding of vaccines in the practise of Naturopathy. Vaccines are part of the practise of Naturopathy and public health in general, so they are not against public health protocols in a global pandemic, according to the respondents.